Neoliberal Multiculturalism, Outsourced - Nadkarni, Asha (The Routledge Companion to Global Television, 2019)
This essay examines the 2010 NBC situation comedy Outsourced, with special attention to its representation of the racial politics surrounding business process outsourcing to India. Specifically, it discusses how Outsourced participates in what Jodi Melamed calls “neoliberal multiculturalism” to work through, symbolically and narratively, the realities and contradictions of globalized economies as they are experienced. By staging the dilemmas of outsourcing through the specter of the white male middle manager traveling to India to train Indian call center workers, Outsourced minimizes the affective labor necessarily performed by Indian call center workers and dramatizes outsourcing as a crisis of white U.S. masculinity alone. Moreover, it figures our white male protagonist as the global multicultural citizen to be emulated insofar as he models the appropriate attitude toward outsourcing and toward “other” cultures in general. Finally it suggests that the failure of the show has less to do with issues of cultural stereotyping and more to do with the failure of neoliberal multiculturalism to soothe anxieties around changing global economies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Curating Life, Staging Art: Modernisms and the Art Practices of Television - Makhubu, Nomusa (The Routledge Companion to Global Television, 2019)
Television is predisposed to the perception that it is the opposite of art and politics and that it is a time-consuming means for “dumbing down,” placating, disempowering and benumbing the citizenry. Through a discussion of the place of art and that of television, I use, as a conceptual framework, the convergence of the white cube and the black box to interrogate dynamics of postcoloniality, vision and power and how this forged divergent modernisms. Television in Africa did not, as with postwar America, create a sense of collective communities of spectatorship that would be brought closer to art appreciation through television. Rather, television, as the political, social and cultural phenomenon of modernization in various African countries, seemed to corrupt what was regarded as “pristine” cultural practices. However, since it coincided with colonial independence and the emergence of postcolonial nations, it became intertwined with various modes and mediums through which new forms of social consciousness aimed at self-definition and self-representation could be disseminated. The convergence of the white cube spaces of art and the black box of television enables an engagement with the colonial spatio-temporal distanciation of Africa from the global stage.
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; Afrique du Sud (lieu de production du savoir); _Nettoyé

African Television in the Age of Globalization, Digitization, and Media Convergence - Eko, Lyombe (The Routledge Companion to Global Television, 2019)
African television is at the crossroads. This chapter surveys, describes, analyzes and explains the major changes that have taken place in the African television landscape since the 1990s. It focuses on three major developments that have marked the African television landscape: (1) liberalization of the television space to keep abreast of international developments, and the tension between entrenched governmental public broadcasting systems and newly licensed “independent” TV stations, (2) the process and impact of the analogue to digital TV switchover shepherded by the International Telecommunications Union, and (3) the diffusion of Chinese electronic technology, television, and film content on the African television market as part of the Asian giant’s “soft power” diplomacy and State capitalism. African television is constrained by political regimes that restrict freedom of expression, and regulatory agencies that preside over systems in which the law takes precedence over rights.
Keywords: 1-TV; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (lieu de production du savoir)